Creating the conditions for entrepreneurial learning within an inclusive and scalable African business education ecosystem - Hosken, Christopher (Graduate School of Business (GSB), 2020)
Entrepreneurship is key to growing and uplifting emerging economies like South Africa. There exists an extremely high failure rate amongst entrepreneurs in this country, this coupled with a lack of support for entrepreneurs, creates the conditions where an entrepreneurial culture cannot thrive. Entrepreneurship and education can be South Africa's most significant tools of liberation and unlock exponential growth which can, in turn, address the socio-economic problems that exist. This research aims to understand what the critical educational and support elements are that drive entrepreneurial learning and development. This research aims to discover what is required to create meaningful learning experiences for entrepreneurs and how this learning can be turned to practice and drive entrepreneurial growth. This growth may play a key role in addressing some of the gaps that exist between South Africa's entrepreneurial potential and its current state. Online and virtual education technologies, pedagogies and methodologies are explored as the core proponents of these learning experiences. Different models are explored and analysed in their distinct contexts to discover what it takes to create these learning experiences. New models of entrepreneur education and the supporting technology are examined to help understand how entrepreneur education programmes can create meaningful learning and development that produces and support high potential entrepreneurs. The research primarily explores an innovative model of an online entrepreneurship education offering that attempts to exponentially improve the impact of traditional models. An adapted design thinking methodology is applied; this allowed the study to examine various models and phenomena through a hyper-practical lens. This methodology supported the research process in uncovering what challenges exist for an education model of this nature to develop meaningful learning and development opportunities for entrepreneurs. 5 The impact of this research could be widespread in assisting with the understanding of how entrepreneurs learn and apply knowledge. The literature reviewed aimed to provide a view of what trends exist in social entrepreneurship globally and South Africa, and how these trends link to meaningful entrepreneurial learning and practice. This research is unique in that it takes a nascent concept such as virtual ecosystems in the social entrepreneurial context and explores how a model in which deep learning experiences are present for entrepreneurs, affects meaningful development and entrepreneurial outcomes. This research focuses on building theory through qualitative data sources collected through the research instruments of interviews, questionnaires, observations, discussions and practical prototyping.